Spectral Diversity of Rocks and Soils in Mastcam Observations Along the Curiosity Rover's Traverse in Gale Crater, Mars. Issue 8 (22nd August 2022) - Rice, Melissa S.; Seeger, Christina; Bell, Jim; Calef, Fred; St. Clair, Michael; Eng, Alivia; Fraeman, Abigail A.; Hughes, Cory; Horgan, Briony; Jacob, Samantha; Johnson, Jeff; Kerner, Hannah; et al.
Abstract: The Mars Science Laboratory Curiosity rover has explored over 400 m of vertical stratigraphy within Gale crater to date. These fluvio‐deltaic, lacustrine, and aeolian strata have been well‐documented by Curiosity's in situ and remote science instruments, including the Mast Camera (Mastcam) pair of multispectral imagers. Mastcam visible to near‐infrared spectra can broadly distinguish between iron phases and oxidation states, and in combination with chemical data from other instruments, Mastcam spectra can help constrain mineralogy, depositional origin, and diagenesis. However, no traverse‐scale analysis of Mastcam multispectral data has yet been performed. We compiled a database of Mastcam spectra from >600 multispectral observations and quantified spectral variations across Curiosity's traverse through Vera Rubin ridge (sols 0–2302). From principal component analysis and an examination of spectral parameters, we identified nine rock spectral classes and five soil spectral classes. Rock classes are dominated by spectral differences attributed to hematite and other oxides (due to variations in grain size, composition, and abundance) and are mostly confined to specific stratigraphic members. Soil classes fall along a mixing line between soil spectra dominated by fine‐grained Fe‐oxides and those dominated by olivine‐bearing sands. By comparing trends in soil versus rock spectra, we find that locally derived sediments are not significantly contributing to the spectra of soils. Rather, varying contributions of dark, mafic sands from the active Bagnold Dune field is the primary spectral characteristic of soils. These spectral classes and their trends with stratigraphy provide a basis for comparison in Curiosity's ongoing exploration of Gale crater. Plain Language Summary: The Curiosity rover's Mastcam instrument is a pair of cameras that take images in visible and near‐infrared wavelengths. Mastcam spectra can distinguish between different types of iron‐bearing minerals. During Curiosity's traverse through a variety of sedimentary rock types in Gale crater, Mars, the rover has acquired more than 600 Mastcam multispectral observations, but no previous studies have analyzed the full data set. In this study, we compiled a database of Mastcam spectra from the first 2302 sols (Martian days) of Curisoity's mission and analyzed spectral trends across the traverse. We define nine classes of spectra for rocks and five classes of spectra for soils, and we observe that different classes occur in different locations. The major spectral differences are due to the mineral hematite and other iron oxides. By comparing the trends in rock spectra to nearby soils across the traverse, we find that the soils are not made of the same minerals as the local rocks, but are dominated by sands from the active Bagnold Dune field. These spectral classes and their trends will be a basis of comparison for Curiosity's ongoing exploration of Gale crater. Key Points: The diversity in Mastcam multispectral data from sols 0–2302 is encapsulated by nine rock spectral classes and five soil spectral classes The major spectral differences in Mastcam spectra across Curiosity's traverse are attributable to hematite and other Fe‐oxides Comparisons of soil versus rock spectra indicate that locally‐derived sediments are not significantly contributing to the spectra of soils